Association between the fetal cerebroplacental ratio and biomarkers of hypoxia and angiogenesis in the maternal circulation at term. (February 2020) - Irvine, Katharine M.; Bligh, Larissa N.; Kumar, Sailesh
Abstract: Objectives: A low fetal cerebroplacental ratio (CPR) in late pregnancy is a marker of a fetus that has failed to reach its growth potential and is associated with a variety of perinatal and pregnancy complications. It is not known if it is also correlated with aberrations in angiogenic, hypoxia-responsive or inflammatory cytokine levels in the maternal circulation. We investigated if there were any differences in levels of biomarkers of angiogenesis, endothelial cell dysfunction, hypoxia and/or inflammation in term pregnancies with a low fetal CPR compared to controls. We hypothesized that as the CPR is a marker of suboptimal growth, this would be reflected in a shift towards upregulation of hypoxia-responsive factors even in non-small for gestational age fetuses. Study design: We used Multiplex ELISA to measure a panel of 28 candidate biomarkers of angiogenesis and/or hypoxia in pre-labour maternal plasma from 113 women at term, stratified for CPR <10th centile vs. CPR >10th centile. Plasma levels of the biomarkers were measured using 2 multiplex Luminex assays - a commercially available human angiogenesis/growth factor panel (R&D Systems®), comprising 15 analytes and an in-house custom panel of a further 13 candidate biomarkers. Results: Of the 28 candidate biomarkers investigated, we found significantly elevated levels of Carbonic Anhydrase 9 and soluble Fms-like tyrosine kinase (Vascular Endothelial Growth Factor Receptor 1), and lower levels of Placental Growth Factor in plasma from women with a low fetal CPR. The soluble Fms-like tyrosine kinase-1/Placental Growth Factor ratio was also markedly elevated in this cohort. We also demonstrated significant inverse correlations between the fetal CPR and Carbonic Anydrase 9, soluble Fms-like tyrosine kinase and Hepatocyte Growth Factor. Conclusions: A low fetal CPR is associated with changes in some hypoxia-responsive and angiogenesis factors in the maternal circulation in pregnancies with normally grown fetuses.